Lead (Pb++) effect on human atrial action potential under normal and atrial fibrillation conditions. In silico study (2017)
Lead (Pb++) is a toxic agent that can exert adverse effects on the cardiac human health. Pb++ blocks the Ltype Ca++ channels. A decrease in L-type calcium current (ICaL) is an important mechanism favoring atrial fibrillation. It is important to study the electrophysiological Pb++ effects on the atrial action potential in healthy people and those with AF. For this, we study the consequences of Pb++ on action potential, under normal and atrial fibrillation condition using in silico models. Our results suggest that Pb++ blocks ICaL current in a fraction greater as the concentration increases, resulting in an action potential duration shortening, Pb++ has a greater action potential duration effect on control conditions. To our knowledge, this is the first work that has developed mathematical models of Pb++ effect on ICaLcurrent to study its effect on human atrial action potential. © Springer Nature Singapore Pte Ltd. 2017.